55.3k views
0 votes
Simplify the below equation

( {8x^(2) y^(3) )( (3)/(8)x {y}^(4) )


2 Answers

5 votes

Answer:

3x^3y^7.

Explanation:

8 * x^2 * y^3 * 3/8 * x * y^4

= 8 * 3/8 * x^2 * x * y^3 * y^4

= 3x^3y^7.

User Andrey Kuzmin
by
5.1k points
6 votes

Answer:

3x^3y^7

Explanation:

( 8 x^2 y^3) *( 3/8 x y^4)

Multiply the coefficients

8 * 3/8 = 3

Multiply the x terms

x^2*x = x^3

Multiply the y terms

y^3 * y^4 = y^(3+4) = y^7

Put them back together

3x^3y^7

User Meli
by
5.4k points